Humoral and cellular immune responses to Blomia tropicalis and concanavalin A-binding fractions in atopic patients - Alves,R. (2008)
Blomia tropicalis, Dermatophagoides pteronyssinus and D. farinae are prevalent house dust mites. Concanavalin A-binding components derived from B. tropicalis (Bt-ConA extract) are highly immunogenic in allergic diseases. The aim of the present study was to evaluate the humoral and cellular immune responses to B. tropicalis in mite-sensitized patients. A total of 137 patients with allergic rhinitis with/without asthma and 109 non-atopic subjects were selected and analyzed by the skin prick test, and for total serum IgE and specific IgE levels to both Bt-total and Bt-ConA extracts, their proliferative response and cytokine (IFN-γ and IL-5) production by peripheral blood mononuclear cells (PBMC) stimulated with both extracts. Skin prick test showed that 70% of the patients were sensitized to Bt (Bt+) and similar levels of specific IgE to Bt-total and Bt-ConA extracts were demonstrable in Bt+ patients. Significant PBMC proliferation was observed in response to Bt-total extract in Bt+, but not in Bt- patients and non-atopic subjects (P < 0.001). Bt-ConA extract induced increased proliferative responses in all patient groups compared to medium alone (P < 0.05), but these responses were significantly decreased in the presence of the mannopyranoside ConA inhibitor (P < 0.05). Significant IFN-γ production was observed after Bt-ConA stimulation of Bt+ patients (P < 0.05), while Bt-total extract had no effect. IL-5 production was consistently detected in Bt+ patients after allergen-specific stimulation or with no stimulus, indicating that PBMC from allergic patients are prone to produce Th2 profile cytokines, spontaneously or inductively by allergen restimulation. These data showed that ConA-binding components isolated from B. tropicalis may contain relevant antigens that are involved in both humoral and cellular immune responses. However, without an additional purification procedure to eliminate the residual contamination with ConA, its use in immunotherapeutic procedures cannot be recommended.